Evaluation of 3D failure modes in CFRP composite laminates - Liu, Zhe (2016)
Wind power is the most successful and cost effective technology for clean energy production. Currently most of wind turbine blades are made of fiber reinforced polymer (FRP) composites. In order to provide useful information to researchers for optimized design of multidirectional FRP composite structures, it is vital to investigate the static and fatigue behaviors of FRP composites associated with failure mechanisms, which is the aim of this research. Specifically, the contents of this thesis are as follows: Firstly, the tensile and fatigue behaviors of three kinds of carbon fiber reinforced polymer (CFRP) laminates with stacking sequences of [0/+45/-45]s, [+45/-45/0]s and [+45/-45/0]2s that have been extensively used by wind blade manufacturers were investigated. Results show that the fatigue performance of the [+45/-45/0]s laminate is more excellent than [0/+45/-45]s laminate. Comparing [+45/-45/0]s laminate and [+45/-45/0]2s laminate, the predicted fatigue strength at 1 million cycles for the latter is just a little higher than that for the former. The effect of embedded delamination location on the flexural behaviors of CFRP laminates with symmetric layup sequence of [+45/-45/0]2s were investigated. Results show that the embedded delamination with the same size at different positions or interfaces has different extent of negative effects on the flexural strength of [+45/-45/0]2s CFRP laminates, but exerts no effects on the initial flexural modulus of elasticity of the laminates. After failure, all the specimens were reloaded to obtain the residual properties. It might be concluded that the reduction ratio of the initial flexural modulus is positively correlated with the areas of parallel damage (whose plane is parallel to the loading direction) and the reduction ratio of the flexural strength is almost positively correlated with the area of all the damage. After investigation of static flexural behaviors, the flexural fatigue behaviors of the [+45/-45/0]2s CFRP laminate composites were studied. Results show that the flexural fatigue life at failure can be quantitatively determined by the cycle when the tracked secant stiffness degrades by 21%. The two-parameter Weibull distribution well represents the statistical nature of the fatigue life data of the CFRP laminate. Combined with the Sigmoidal model, the Weibull analysis method reliably predicts the fatigue life as a function of the applied deflection level. Lastly, the effects of fiber orientation of adjacent plies on the mode I interlaminar fracture behaviors were studied. Results show that computed tomography (CT) scans enabled an insight into the real crack fronts of the three kinds of specimens after DCB tests. The mode I interlaminar fracture toughness at the initial stage (Ginit) is almost the same for 0//0, 0//45 and 45//-45 interfaces. While the toughness at the crack propagation stage (Gprop) in specimens with 0//0, 0//45 and 45//-45 interface continuously increases. Besides, the numerical model with variable fracture toughness is applicable to represent the mode I interlaminar fracture toughness of the FRP specimens and in good agreements with the experiments.